Gentree of Tool for Syntactic Analysis Based On Younger Cocke Kasami Algorithm - - Wijanarto; Ajib Susanto; Desi Purwanti Kusumaningrum (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Syntactic analysis is a series of processes in order to validate a string that is received by a language. Understanding the process of reduction rules to become a tree is the part that is difficult to explain. This paper describes the results of the design tool to automate an input string into a decrease in the rules to trees in the visualized with images either in the form of files or display, performance evaluation tools and analysis of students' understanding of the tool by the algorithm Cocke Younger Kasami (cyk) was selected as one of the cases for parsing techniques in the Context Free Grammar (CFG) in the form of Chomsky Normal Form (CNF). These results indicate that the model successfully implemented into the application named genTree (Generator Tree), application performance gained a significant number of measurements of the variations in the complexity of the grammar and the input string by 29.13% with the complexities 7 and 8:50% with the complexity of 20, while for long input string against time processing algorithm can be a value of 3.3 and 66.98% as well as 29 and 6:19%, also obtained differences in the ability of the t-test on a group of students control against the experimental group with a value of t = 5.336 with df 74, p value of 0.001 , on the level of signfikansi 0.05% (5%). Also terapat increase in the percentage of correct answers was 58% in the variation of difficulty, 83% of the variation was easy. Sebalikanya wrong answer decline by 60% in difficult variation, the variation was 100% and 57% for easy variation. Recently there is a change decrease in the percentage of students who are not doing as much as 60% in the variation of difficulty, 44% of the variation was 13% on the variations easily can be concluded that the applications run efficiently and optimally, but also can effectively improve students' understanding in beajar automata with case cyk algorithm. Keywords—Tool, Analysis, Syntax, Algorithms, Trees